Silicon Supply Improves Nodulation and Dinitrogen Fixation and Promotes Growth in Trifolium incarnatum Subjected to a Long-Term Sulfur Deprivation - Raphaël Coquerel; Mustapha Arkoun; Quentin Dupas; Fanny Leroy; Philippe Laîné; Philippe Etienne (Plants, 2023)
In many crops species, sulfur (S) deprivation negatively affects growth, seed yield quality and plant health. Furthermore, silicon (Si) is known to alleviate many nutritional stresses but the effects of Si supply on plants subjected to S deficiency remain unclear and poorly documented. The objective of this study was to evaluate whether Si supply would alleviate the negative effects of S deprivation on root nodulation and atmospheric dinitrogen (N2) fixation capacity in Trifolium incarnatum subjected (or not) to long-term S deficiency. For this, plants were grown for 63 days in hydroponic conditions with (500 µM) or without S and supplied (1.7 mM) or not with Si. The effects of Si on growth, root nodulation and N2 fixation and nitrogenase abundance in nodules have been measured. The most important beneficial effect of Si was observed after 63 days. Indeed, at this harvest time, a Si supply increased growth, the nitrogenase abundance in nodules and N2 fixation in S-fed and S-deprived plants while a beneficial effect on the number and total biomass of nodules was only observed in S-deprived plants. This study shows clearly for the first time that a Si supply alleviates negative effects of S deprivation in Trifolium incarnatum.